Primary cilia in Parkinson’s disease: summative roles in signaling pathways, genes, defective mitochondrial function, and substantia nigra dopaminergic neurons - Tian, Zijiao; Zhang, Yixin; Xu, Jing; Yang, Qianwen; Hu, Die; Feng, Jing; Gai, Cong (Frontiers in Aging Neuroscience, 2024)
Primary cilia (PC) are microtubules-based, independent antennal-like sensory organelles, that are seen in most vertebrate cells of different types, including astrocytes and neurons. They send signals to cells to control many physiological and cellular processes by detecting changes in the extracellular environment. Parkinson's disease (PD), a neurodegenerative disease that progresses over time, is primarily caused by a gradual degradation of the dopaminergic pathway in the striatum nigra, which results in a large loss of neurons in the substantia nigra compact (SNpc) and a depletion of dopamine (DA). PD samples have abnormalities in the structure and function of PC. The alterations contribute to the cause, development, and recovery of PD via influencing signaling pathways (SHH, Wnt, Notch-1, α-syn, and TGFβ), genes (MYH10 and LRRK2), defective mitochondrial function, and substantia nigra dopaminergic neurons. Thus, restoring the normal structure and physiological function of PC and neurons in the brain are effective treatment for PD. This review summarizes the function of PC in neurodegenerative diseases and explores the pathological mechanisms caused by PC alterations in PD, in order to provide references and ideas for future research.